A highly active Cp*Ir complex with an anionic N, N-donor chelate ligand catalyzes the robust regeneration of NADH under physiological conditions. Issue 24 (10th November 2021) - Zhao, Li-Jun; Yin, Zequn; Shi, Yusheng; Sun, Wen; Sun, Libo; Su, Huijuan; Sun, Xun; Zhang, Weiling; Xia, Linyan; Qi, Caixia
Abstract : Anionic N, N-donor ligand chelate iridium complex [Cp*Ir(pba)Cl] 3 was developed, and exhibited the highest activity for NADH regeneration so far and stable chemoenzymatical coordinate catalytic performance for acetophenone enantioselective hydrogenation. Abstract : A highly active [N^N − ] iridium complex [Cp*Ir(pba)Cl] (3, Cp* = pentamethylcyclopentadiene, pba = 4-(picolinamido)benzoic acid) has been obtained with an anionic ligand, which exhibited the most robust performance for cofactor NADH regeneration in physiological conditions with HCOONa as the hydrogen source. The structure of complex 3 was revealed by X-ray single-crystal structure analysis. The turnover frequency (TOF) of complex 3 in the regeneration of NADH is 7825 h −1, which is about 22.7 times and 178 times higher than that of the C − ^N type complex 2 (345 h −1 ) and N^N complex 1 (44 h −1 ) at 37 °C, respectively. The high activity of complex 3 seems to be critically affected by the negatively charged N − of the amide chelating ligand, which could promote the reaction rate of Ir–Cl conversion to Ir–H2 O. Furthermore, complex 3 shows good biocompatibility for various biomolecules except SH-compounds (such as reduced glutathione (GSH)). When combined with NADH-dependent enzymes (KRED-101), the complex 3 -based NADH-regeneration catalytic system shows stable chemoenzymatical coordinate catalytic activity for reducing acetophenone to the corresponding alcohol with high enantioselectivity.